Shift of the macroscopic characteristics of thermodynamic systems under the influence of radiation - Gavryushenko, D. A.; Taradiy, K. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The influence of radiation emission on the physical systems results in the new components, which appear in these systems. These components differ from the initial ones by the interaction energy, as well as by physicalproperties of particles. For this reason, the correlation function formalism appears to be the most convenient. It allows not only to evaluate shifts of the main macroscopic parameters, but also to clearly interpret the structure changes caused by irradiation. A number of important equations, which represent the macroscopic parameters of the system through corresponding correlation functions, are obtained.